Project Report on Design and Development of Infrared Optical Communication System for Wireless Audio Transmission Over a Distance of Upto One Kilometer - AMAR K R, MON VARGHESE, CHANDRAN J, KALYAN S GOSWAMI, YUVARAJ K S, NIMA B and VINODKUMAR T (1999)
INTERNAL GUIDE: R BABU , MVJCE
Keywords: Design and Development of Infrared Optical Communication System for Wireless Audio Transmission Over a Distance of Upto One Kilometer